Re-telling a story in a second language: How well do adult learners mine an input text for multiword expressions? - Hoang, Hien; Boers, Frank (Studies in Second Language Learning and Teaching, 2016)
Adult second language (L2) learners have often been found to produce discourse that manifests limited and non-native-like use of multiword expressions. One explanation for this is that adult L2 learners are relatively unsuccessful (in the absence of pedagogic intervention) at transferring multiword expressions from input texts to their own output resources. The present article reports an exploratory study where ESL learners were asked to re-tell a short story which they had read and listened to twice. The learners’ re-tells were subsequently examined for the extent to which they recycled multiword expressions from the original story. To gauge the influence of the input text on these learners’ renderings of the story, a control group was asked to tell the story based exclusively on a series of pictures. The results of the experiment suggest that multiword expressions were recycled from the input text to some extent, but this stayed very marginal in real terms, especially in comparison with the recycling of single words. Moreover, when learners did borrow expressions from the input text, their reproductions were often non-target-like.